Hubungan Pemakaian Kontrasepsi Hormonal Dengan Gangguan Menstruasi Di Puskesmas Kebonsari Kota Pasuruan - Ilminingtyas, Pratnya (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2009)
the design of this study is analytical by using cross sectional approach, with the population of 40 acseptors of familly planning on june 2008. sampling technique wich is used is random sampling technique, in wich there are 37 respondents with the questionairre on menstruation disturbance and contraception identity card in order to know the contraception used.the result of the study showed that the respondens which were using combination hormonal contraception and having menstruation disturbance